2012
DOI: 10.4161/cbt.13.4.18694
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 downregulates vimentin and inhibits breast cancer cell invasion

Abstract: Vimentin, a mesenchymal marker, is frequently overexpressed in epithelial carcinomas undergoing epithelial to mesenchymal transition (EMT), a condition correlated with invasiveness and poor prognosis. Therefore, vimentin is a potential molecular target for anticancer therapy. Emerging studies in experimental models underscore the functions of homeodomain-interacting protein kinase 2 (HIPK2) as potential oncosuppressor by acting as transcriptional corepressor or catalytic activator of molecules involved in apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…This result is consistent with previous studies, in which HIPK2 downregulation has been reported in bladder cancer, breast cancer and ovarian cancer (12,14,22). HIPK2 overexpression has also been demonstrated in patients with cervical and colorectal cancer with familial adenomatous polyposis (23,24).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result is consistent with previous studies, in which HIPK2 downregulation has been reported in bladder cancer, breast cancer and ovarian cancer (12,14,22). HIPK2 overexpression has also been demonstrated in patients with cervical and colorectal cancer with familial adenomatous polyposis (23,24).…”
Section: Discussionsupporting
confidence: 82%
“…Chung et al (29) previously reported that N-cadherin suppresses RAC-γ serine/threonine-protein kinase to promote cell motility in mammary tumor cells. Furthermore, Qian et al (30) demonstrated that N-cadherin served a pivotal role in promoting metastasis through the regulation of extracellular-regulated kinase and protein kinase B. Nodale et al (14) demonstrated that MDA-MB-231 cells transfected with HIPK2 had decreased levels of vimentin mRNA that strongly correlated with re-expression of E-cadherin, which is indicative of a reversion of the EMT phenotype. Tan et al (15) also demonstrated that HIPK2 knockdown increased the levels of the mesenchymal markers N-cadherin and fibronectin and decreased the level of E-cadherin, indicating that EMT is induced by HIPK2 downregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIPK2 was required for the Fbw7‐dependent proteasomal degradation of Notch1 by phosphorylating its intracellular domain, suggesting that HIPK2 regulates tumor progression . Additionally, vimentin downregulation by HIPK2 correlated with inhibition of breast tumor cell invasion . In heterozygous p53 ‐deficient background, mice with heterozygous loss of HIPK2 gene developed more lymphomas after irradiation than those with wild‐type HIPK2 gene .…”
Section: P53 Phosphorylation In Tumor Suppressive Rolesmentioning
confidence: 99%
“…67 Additionally, vimentin downregulation by HIPK2 correlated with inhibition of breast tumor cell invasion. 68 In heterozygous p53-deficient background, mice with heterozygous loss of HIPK2 gene developed more lymphomas after irradiation than those with wild-type HIPK2 gene. 69 These findings indicate that HIPK2 is a promising target for cancer treatment.…”
Section: Suppressive Rolesmentioning
confidence: 99%